FOCUS ON THE LEADER PROGRAMME… PAST, PRESENT, AND FUTURE? - Máté, Péter; Tóth, Tamás (Studia Mundi – Economica, 2022)
Many have already described that truly effective future creation cannot do without an exploration of the past, and that there is no point in avoiding clarifying and evaluating the processes that have already taken place in this field, if only because they can provide many lessons, both in terms of mistakes made and good practices developed. In the context of the LEADER programme, we have compiled a selection of the most important events and processes, with the intention of highlighting the key achievements that have been made. In addition, we would like to highlight the less successful activities and operational anomalies whose continuation is not conducive to a smooth process of community building and rural development. The LEADER programme has undergone a number of changes and we believe that these changes have had many benefits in terms of improving the living conditions of rural people, but the scheme has yet to deliver real community-building effects. Unfortunately, in many cases the programmes have been implemented to serve individual interests rather than to build community.